PERANCANGAN SISTEM INFORMASI KEMATIAN DENGAN MENGGUNAKAN MICROSOFT VISUAL STUDIO2010PADA RUMAH SAKIT TK II 03.05.01 DUSTIRA CIMAHI - Edi Suharto; Maria Yunita Ona; Lailela, Septi Noer (INFOKOM (Informatika & Komputer), 2019)
This study aimed to design the information sytem death using Microsoft Visual Studio 2010 at hospital TK II. 03.05.01 Dustira Cimahi Hospital.. The research method used a qualitive research method with a descriptive approach. Data collection techniques used field work practices, interview, and book study. Development method used is waterfall model. Based on the of the author observations during field work practice at TK II. 03.05.01 DUSTIRA CIMAHI HOSPITAL, the problems foudd are death information certificate sytem were the data was done by using microsoft excel but this is less effective. The problems solving these case, the writer design an information sytem using microsoft visual studio 2010 it was expected to be able to produce an application death certificate information sytem that could solve the proplems that occur. The suggestion from the writer are (1) Making the system more effective to optimize death certificate information sytem in the INFOKES and reoports that the death certificate so is avaible at any time when never needed. (2) Having training for officers who wiil use the death certificate information system.